Short-Term Tinnitus Suppression With Electric-Field Guided rTMS for Individualizing rTMS Treatment: A Technical Feasibility Report - Schoisswohl, Stefan; Langguth, Berthold; Schecklmann, Martin (Frontiers in Neurology, 2020)
Background: Past research highlighted the benefits of personalized repetitive transcranial magnetic stimulation (rTMS) for the treatment of chronic subjective tinnitus. Objective/Hypothesis: The objective was to investigate the feasibility of rTMS personalization by identifying individually optimal stimulation parameters in test sessions. Particularly, effectiveness and retest–reliability of different stimulation parameters were examined. Methods: Via electric-field guided rTMS, five patients were stimulated with different frequencies on three positions of the left and right superior temporal gyrus on 2 separate days. After each stimulation, the patients had to evaluate tinnitus loudness and discomfort of the used protocol. Results: Individualization of rTMS was possible in all five patients. Significant lower tinnitus loudness was found for 1 Hz stimulation. Positive correlations between 2 days were observed for hemisphere (left, right), position (mSTG, pSTG), and frequency (1, 10, 20 Hz). High-frequency stimulation produced high discomfort. Conclusion: Personalization of rTMS is considered as feasible. Consistency of parameter-specific tinnitus suppression is demonstrated.